Dilapidation inspection project at Damansara / Mohamad Zulkifli Mazlan - Mazlan, Mohamad Zulkifli (Universiti Teknologi Mara, Perak, 2018)
Dilapidation inspections are defined as an inspection and report on the condition of a property at a given point in time. It records any existing damage and the state of any particular aspects of the property that are likely to be affected by construction work, excavation or demolition. This report will discuss about the dilapidation survey of Damansara project. This project is personal request by the owner building themself. This is because the owner is not satisfied with the work of building surveyor that have do inspection on the building hired by the contractor of construction nearby. The dilapidation survey done in this report is located at no. 54, Jalan Balau, Bukit Damansara, 50490 Kuala Lumpur. It will focus on the important aspects needed to be taken into account and contains detail explanation of the work process and procedure while the dilapidation survey is carried out during construction in which Jasa Sendi (M) Sdn. Bhd., the subcontractor specialized for dilapidation survey has been appointed by Dato Lah Siew Cheang. The inspection is done by going through along the infrastructures and buildings. Methods of study used for this report is through observation at site, on-hand training, and literature reviews. Information are gathered to broaden understanding and to get a clear picture and visual about the topic being discussed. The results of this inspection will analyse the importance and criteria of dilapidation survey as well discovers the equipment and skill used during inspection.